2015
DOI: 10.26719/2015.21.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer screening programme: experience from Eastern province, Saudi Arabia

Abstract: Programmes for early diagnosis of breast cancer are lacking in most countries in the Eastern Mediterranean Region. This paper reviews a nongovernmental screening programme launched in October 2009 in the Eastern Province of Saudi Arabia, in which 14 health centres were covered by 2 mobile mammography machines. Annual screening was offered to all women aged 40 years and above. Up to February 2014 a total of 8061 women were screened, an uptake rate of 15.0%. The recall rate was 7.9%. The number of cancers detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 9 publications
0
25
1
Order By: Relevance
“…The mean age of patients with breast cancer was significantly higher than of the controls ( p <0.05). However, the mean age of these patients in the current study was 5-10 years lower than that reported in the Saudi Cancer Registry 25 and the study by Al Mulhim et al 26 In addition to age, the World Health Organization, 27 also reported that other factors associated with breast cancer risk include late age at marriage, early menarche, late menopause, and long menstrual history. Our findings revealed a later age at menopause in patients with breast cancer than in controls, which is in line with previous findings.…”
Section: Discussioncontrasting
confidence: 67%
“…The mean age of patients with breast cancer was significantly higher than of the controls ( p <0.05). However, the mean age of these patients in the current study was 5-10 years lower than that reported in the Saudi Cancer Registry 25 and the study by Al Mulhim et al 26 In addition to age, the World Health Organization, 27 also reported that other factors associated with breast cancer risk include late age at marriage, early menarche, late menopause, and long menstrual history. Our findings revealed a later age at menopause in patients with breast cancer than in controls, which is in line with previous findings.…”
Section: Discussioncontrasting
confidence: 67%
“…For screening programs to be successful at the population level, strategic implementation should be coordinated at the national level and include educational components, as well monitoring and evaluation to ensure success and sustainability. Opportunistic screening programs in the past have been hampered by low participation rates due to anxiety, misperception of the screening’s purpose, and a general sense that cancer at any stage is a death sentence (Al Mulhim et al 2015 ; Al-Zalabani et al 2016 ). Civil engagement through education and advocacy is therefore an important pillar of successful and sustainable screening programs.…”
Section: Discussionmentioning
confidence: 99%
“…From 2009-2010, the program covered only four centers, and 14 centers were covered by October 2013. 18 …”
Section: Discussionmentioning
confidence: 99%